Targeting Wnt signaling for improved glioma immunotherapy - Gutova, Margarita; Hibbard, Jonathan C.; Ma, Eric; Natri, Heini M.; Adhikarla, Vikram; Chimge, Nyam-Osor; Qiu, Runxiang; Nguyen, Cu; Melendez, Elizabeth; Aguilar, Brenda; Starr, Renate; Yin, Holly; et al. (Frontiers in Immunology, 2024)
Despite aggressive standard-of-care therapy, including surgery, radiation, and chemotherapy, glioblastoma recurrence is almost inevitable and uniformly lethal. Activation of glioma-intrinsic Wnt/β-catenin signaling is associated with a poor prognosis and the proliferation of glioma stem-like cells, leading to malignant transformation and tumor progression. Impressive results in a subset of cancers have been obtained using immunotherapies including anti-CTLA4, anti-PD-1, and anti-PD-L1 or chimeric antigen receptor (CAR) T cell therapies (1). However, the heterogeneity of tumors, low mutational burden, single antigen targeting, and associated antigen escape contribute to non-responsiveness and potential tumor recurrence despite these therapeutic efforts (2). In the current study, we determined the effects of the small molecule, highly specific Wnt/CBP (CREB Binding Protein)/β-catenin antagonist ICG-001, on glioma tumor cells and the tumor microenvironment (TME)--including its effect on immune cell infiltration, blood vessel decompression, and metabolic changes. Using multiple glioma patient-derived xenografts cell lines and murine tumors (GL261, K-Luc), we demonstrated in vitro cytostatic effects and a switch from proliferation to differentiation after treatment with ICG-001. In these glioma cell lines, we further demonstrated that ICG-001 downregulated the CBP/β-catenin target gene Survivin/BIRC5--a hallmark of Wnt/CBP/β-catenin inhibition. We found that in a syngeneic mouse model of glioma (K-Luc), ICG-001 treatment enhanced tumor infiltration by CD3 + and CD8 + cells with increased expression of the vascular endothelial marker CD31 (PECAM-1). We also observed differential gene expression and induced immune cell infiltration in tumors pretreated with ICG-001 and then treated with CAR T cells as compared with single treatment groups or when ICG-001 treatment was administered after CAR T cell therapy.We conclude that specific Wnt/CBP/β-catenin antagonism results in pleotropic changes in the glioma TME (tumor microenvironment), including glioma stem cell differentiation, modulation of the stroma, and immune cell activation and recruitment, thereby suggesting a role for enhancing immunotherapy in glioma patients.